Pengaruh Perlakuan Panas Pada Clad Bend Pipe (API5L) dengan Pengelasan GTAW Overlay Menggunakan UNS N06625 Terhadap Kekuatan Tarik Material - Aulia Fajrin (Jurusan Teknik Mesin Fakultas Teknik Universitas Bangka Belitung, 2022)
Heat Treatment is a process of heating a material (metal) with a certain temperature and then cooling it using certain media (for example: oil, water, and salt water) with a specified cooling speed. This research used a quenching and tempering heat treatment process on API 5L carbon steel pipe with a diameter of 16 inches (406.4 mm) and a pipe thickness of 1,437 inches (36.5 mm), which previously the carbon steel pipe had an overlay welding process on the inside using UNS N06625 filler metal with protective gas of Argon 99.999% to reduce the corrosion rate along the bending process to become Clad Bend Pipe. The purpose of this study is to find out any effects of heat treatment (Quenching and Tempering) to increase the value of the tensile test results on clad bend pipes.